ANALISIS PENGENDALIAN KUALITAS PADA PROSES PRODUKSI REINF RR NO.1 SEAT LEG RR DI PT XX - Shafira Melgandri; Laela Chairani (Fakultas Teknik Universitas Tulang Bawang, 2022)
PT. XX. is a company engaged in the automotive sector, precisely in the production of metal components, always prioritizing and trying to create products with high quality, but in the process until now, reject products are still found both during the production process and after passing inspection, while zero defects become standard in the production process. Based on data obtained from August to November 2021, part number 57835-0K020 is the product with the highest rejects. In this study, quality improvement efforts were carried out using the Statistical Quality Control (SQC) method. Several methods used in this research include normality test of data with Kolmogorov Smirnov, Pareto diagram, np control chart and process capability. The results of this study are the observation data is normally distributed, the weld porous is the dominant type of defect, the control chart is statistically controlled, and the Cp index is around 0.83 and the Cpk is around 0.77 so it can be concluded that the process does not have a good capability. Keywords: SQC, Normality Test, Control Chart, CP, Cpk